Hubungan Antara Kontrol Diri dengan Perilaku Konsumtif pada Mahasiswi Prodi Psikologi Universitas Muhammadiyah Sidoarjo - Kharimah, Ismi Izzatul; Hanif, Aisha (ResearchJet Journal of Analysis and Inventions, 2024)
Changes in social culture among student are the cause of consumtive behavior in the university environment. This study ais to determine the relationship between self control and consumtive behavior in psychology program student, university of muhammdiyah sidoarjo. The variables contained in this study are self control as the independent variable and consumtive behavior as the dependent variable. This reliability of the self control scale is 0.891 and the consumtive behavior scale is 0.916. data analysis was performed using person correlation coefficient of -0.451 with a significance of 0.000 <0.05. it can be concluded that there is a negative relationship between self control and consumtive behavior. This mean that the heigher the self control, the lower the consumtive behavior experienced by psychology student at the university of muhammadiyah sidoarjo, on the other hand, if the self control is lower, the consumtive behavior experienced will be higher.